A new species of Varronia P. Browne (Cordiaceae) from central Colombia - Fernández-Alonso, Jose Luis; Miranda De Melo, José Iranildo (Phytotaxa, 2021)
A new species, Varronia teguorum Fern. Alonso & J.I.M. Melo (Cordiaceae), from central Colombia is described. This new taxon is compared morphologically with V. subtruncata and V. bullata, the species with which it is most easily confused. An identification key for the Varronia species with globose inflorescences from Colombia/northern South America is presented.